2011
DOI: 10.1039/c0cp02722g
|View full text |Cite
|
Sign up to set email alerts
|

High-dimensional ab initio potential energy surfaces for reaction dynamics calculations

Abstract: There has been great progress in the development of potential energy surfaces (PESs) for reaction dynamics that are fits to ab initio energies. The fitting techniques described here explicitly represent the invariance of the PES with respect to all permutations of like atoms. A review of a subset of dynamics calculations using such PESs (currently 16 such PESs exist) is then given. Bimolecular reactions of current interest to the community, namely, H + CH(4) and F + CH(4), are focused on. Unimolecular reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
262
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(269 citation statements)
references
References 155 publications
2
262
0
1
Order By: Relevance
“…Reaction dynamics simulations require the knowledge of the PES, which governs the motion of the atoms in a chemical reaction [15][16][17] . Full-dimensional analytical PESs that describe both the back-and front-side attack mechanisms have not been developed for S N 2 reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction dynamics simulations require the knowledge of the PES, which governs the motion of the atoms in a chemical reaction [15][16][17] . Full-dimensional analytical PESs that describe both the back-and front-side attack mechanisms have not been developed for S N 2 reactions.…”
Section: Resultsmentioning
confidence: 99%
“…This composite method provides AE-CCSD(T)/aug-cc-pCVQZ quality results within a root-mean-square error of only 0.35 kcal mol À 1 . The analytical representation of the PES is obtained by a fifth-order fit using the permutationally invariant polynomial approach 15,16 based on Morse-like variables, exp(-r ij /a), where r ij are the inter-atomic distances and a ¼ 3 bohr. The linear leastsquares fit, with weight of E 0 /(E þ E 0 ), where E 0 ¼ 31 kcal mol À 1 and E is relative to the global minimum, provides 3,313 coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…Recent progress in the determination of PESs by ab initio methods [1] has allowed quantum-mechanical (QM) or quasiclassical trajectory treatments of the reaction dynamics to reproduce the integral and differential cross sections (ICSs and DCSs) obtained in high-resolution crossed-beam experiments for prototypical four-atom HD þ OH ! H 2 O þ D [2] and sixatom Cl þ CHD 3 !…”
mentioning
confidence: 99%
“…[69,71,75] Importantly for applications to materials modeling and design, this method has been shown to provide highaccuracy PESs for bulk materials as well as surfaces and nanostructures, [68,69,72,74,76,77] where other highly accurate approaches developed for molecular systems [22,67] are impractical.…”
Section: Review Wwwq-chemorgmentioning
confidence: 99%
“…We have used this strategy in combination with symmetrizing the NN output and found that it works well in as many as 15 dimensions. [26,29] Guo and coworkers [62][63][64][65][66] [22,67] of interatomic coordinates. Interatomic coordinates make this approach systematic and easy to generalize.…”
Section: Symmetry Issuesmentioning
confidence: 99%